2022
DOI: 10.1007/s00068-022-01919-w
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of early versus delayed weight-bearing with intramedullary nailing of tibial shaft fractures: a systematic review and meta-analysis

Abstract: Purpose Early weight bearing (EWB) is often recommended after intramedullary nailing of tibial shaft fractures, however, the risks and benefits have not been critically evaluated in a systematic review or meta-analysis. Therefore, the aims of this study were to perform a systematic review and meta-analysis comparing EWB and delayed weight-bearing (DWB) after intramedullary nailing of tibial shaft fractures and assess the relationship between weight-bearing, fracture union and healing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
5
0
1
Order By: Relevance
“…OA is a chronic degenerative disease that manifests as pain, stiffness, swelling, and ultimately, the loss of normal joint function [ 4 ]. Fractures, particularly those occurring in weight-bearing areas, such as the spine, pelvis, and hip, can inflict severe acute pain, cause chronic discomfort, and reduce mobility, causing considerable loss of independence [ 5 ]. This loss particularly impacts older adults who may already be adversely affected by other health conditions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…OA is a chronic degenerative disease that manifests as pain, stiffness, swelling, and ultimately, the loss of normal joint function [ 4 ]. Fractures, particularly those occurring in weight-bearing areas, such as the spine, pelvis, and hip, can inflict severe acute pain, cause chronic discomfort, and reduce mobility, causing considerable loss of independence [ 5 ]. This loss particularly impacts older adults who may already be adversely affected by other health conditions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Foreign scholars proposed 12 , 13 that early weight bearing in postoperative ankle fracture patients can help accelerate fracture healing, and early postoperative weight bearing will not lead to problems such as loosening of internal fixation, and it is believed that early weight bearing training is advantageous for ankle joint function recovery and fracture healing. Some scholars have confirmed 14 that early weight-bearing is beneficial to fracture healing, shortens fracture healing time, and promotes the recovery of joint function.The results of this study showed that early standing bed participation in weight-bearing training, and anti-gravity running table training intervention for 8 weeks after the increase in bone mineral density, the quality of bone scab score is higher than that of the control group who received conventional treatment, and there is no displacement of the fracture broken end and the phenomenon of loosening of the internal fixation, which suggests that early progressive weight-bearing can help to accelerate the healing of the fracture, which may be related to the stress stimulation of the fracture broken end, which is in line with the previous research findings Consistent. In this experiment, patients were instructed to start anti-gravity running table training from the 4th week onwards, and the results showed an increase in bone density at the 8th week, which was statistically significant compared with the pre-treatment period, proving that early weight-bearing has a promotional effect on the growth of bone density.It has been suggested that exercise training has a positive effect on bone mineral density 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that early verticalization provides a mechanical stress on the vertebral bony tissue, thus stimulating the calcification process, and this most likely facilitates stabilisation of the instrumentation inserted during the arthrodesis procedure. The importance of loading in healing after stabilization surgery has already been highlighted in other types of interventions, such as stabilization after tibial diaphysis fracture [22][23][24][25]. Further studies on a specific population such as those undergoing spinal arthrodesis surgery are needed to better understand the role of loading in the postoperative calcification process.…”
Section: Discussionmentioning
confidence: 99%